2020
DOI: 10.3390/metabo10050192
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Reveals Global Metabolic Changes in the Evolved E. coli Strain with Improved Growth and 1-Butanol Production in Minimal Medium

Abstract: Production of 1-butanol from microorganisms has garnered significant interest due to its prospect as a drop-in biofuel and precursor for a variety of commercially relevant chemicals. Previously, high 1-butanol titer has been reported in Escherichia coli strain JCL166, which contains a modified clostridial 1-butanol pathway. Although conventional and metabolomics-based strain improvement strategies of E. coli strain JCL166 have been successful in improving production in rich medium, 1-butanol titer was severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…, mutL and mutS ) or in proofreading DNA polymerases ( e.g. , dnaQ ), as well as the overexpression of certain dominant-negative mutator alleles of the same genes, are known to result in mutator phenotypes. , Conditional mutator phenotypes have been applied to the phenotypic optimization of MCFs. However, a major problem of these conditional phenotypes is the relatively low control of temporal activity afforded by the cognate devices. A typical drawback of these systems is that the ability to effectively halt DNA mutagenesis is limited, and the cells will continue to mutate even after a desired phenotype is achieved …”
Section: Introductionmentioning
confidence: 99%
“…, mutL and mutS ) or in proofreading DNA polymerases ( e.g. , dnaQ ), as well as the overexpression of certain dominant-negative mutator alleles of the same genes, are known to result in mutator phenotypes. , Conditional mutator phenotypes have been applied to the phenotypic optimization of MCFs. However, a major problem of these conditional phenotypes is the relatively low control of temporal activity afforded by the cognate devices. A typical drawback of these systems is that the ability to effectively halt DNA mutagenesis is limited, and the cells will continue to mutate even after a desired phenotype is achieved …”
Section: Introductionmentioning
confidence: 99%
“…We are convinced that quantitative approaches in metabolite analysis will help to reduce the time required to establish an efficient whole-cell biocatalyst. In this Special Issue, Laviña, et al demonstrated how metabolomics was utilized to characterize adaptive laboratory evolution Escherichia coli strains [ 1 ]. With the targeted strategy, metabolites in the central carbon metabolic pathways were quantified to understand the overall effect of the mutations acquired through evolution to improve 1-butanol production.…”
mentioning
confidence: 99%